Automatic Navigation and Self-Driving Technology in Agricultural Machinery: A State-of-the-Art Systematic Review - Md. Sabbir Hossain; Mostafijur Rahman; Ashifur Rahman; Md. Mohsin Kabir; M. F. Mridha; Jie Huang; Jungpil Shin (IEEE Access, 2025)
The advent of automatic navigation and self-driving technology in agricultural machinery has transformed modern farming by enhancing efficiency and safety. This systematic review aims to evaluate the development, implementation, and impact of self-driving technology in agriculture. We synthesized recent advancements and research findings on the integration of Global Positioning System (GPS), machine learning algorithms, and sensor technologies in agricultural machinery. Key applications of self-driving machinery in planting, harvesting, and field monitoring were explored, with findings showing improvements in farm productivity, reduced operational costs, and enhanced worker safety. Despite the benefits, challenges such as technological barriers, regulatory issues, and infrastructure limitations remain. This review informs stakeholders about the future potential of self-driving technology in promoting sustainable and precision farming practices.